If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2) + -1y = 6 2 + -1y = 6 Solving 2 + -1y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 6 + -2 -1y = 6 + -2 Combine like terms: 6 + -2 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4
| 19x=6(3x-5) | | 2x-2y=7+y | | 6*k+(3*10-8)=(2*3)*k+22 | | (1)-1y=6 | | 8=6x-1 | | 10+-9=9k+10 | | (0)-1y=6 | | -3/7x=12 | | 18.3x-7=35 | | 3j+2c+5k+3l=6.5 | | 5n-37+14=3 | | -9+10k=10+9k | | 5x=7-x | | 54+.09m=38+0.13m | | -2(3+x)=-20 | | 9d+75=5d-45 | | 5x+rx=r | | 2x^2-28x-140=0 | | 6a=132 | | X^2+8x-11=-2 | | -8-6=3x+2-2x | | 3x+16=29 | | 9.1x+23.1=4.2 | | -4y-6+7y+3+y=17 | | 42x^3-30x^2+7x-5= | | X+6=7.20 | | 3a-1=3a-3 | | x/6-2=x-6 | | 6=2x-18 | | 13t+4=19 | | 180=65+b | | 5(3+5x)-4=111 |